Ethnic-Racial Socialization in Mixed Heritage Families: A Grounded Theory Study - Lee, Angel; Iskandar, Amirul (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to explore how parents in mixed heritage families in Malaysia engage in ethnic-racial socialization and transmit cultural identity to their children within the context of a multicultural society. Methods: Using a qualitative grounded theory approach, data were collected through semi-structured interviews with 25 parents from diverse mixed heritage backgrounds residing in Malaysia. Participants were selected through purposive sampling and theoretical saturation guided the endpoint of data collection. Interviews focused on participants’ practices, challenges, and perspectives regarding cultural identity transmission in the home. Verbatim transcripts were analyzed using NVivo software, employing open, axial, and selective coding to generate a conceptual framework grounded in participants’ narratives. Findings: Five main categories emerged: Cultural Identity Transmission, Language and Communication, Navigating Racial Bias, Family Dynamics, and Community and Social Engagement. Parents engaged in intentional practices such as storytelling, celebration of traditions, and bilingual upbringing to reinforce cultural heritage. They also described emotional and strategic responses to racial bias, as well as negotiation between co-parenting and intergenerational influences. Language was both a bridge and a barrier, shaping identity and familial cohesion. Parents sought external support through cultural events and digital communities to validate and enrich their children’s mixed identities. These findings highlight the emotional labor and adaptive strategies involved in raising bicultural children in socially stratified environments. Conclusion: Ethnic-racial socialization in mixed heritage families is a complex, multifaceted process involving intentional practices, emotional negotiations, and contextual adaptations. Parents act as cultural mediators, balancing heritage preservation with societal integration.